2000
DOI: 10.1152/jappl.2000.89.4.1499
|View full text |Cite
|
Sign up to set email alerts
|

Exercise elevates plasma levels but not gene expression of IL-1β, IL-6, and TNF-α in blood mononuclear cells

Abstract: Physical activity induces a subclinical inflammatory response, mediated in part by leukocytes, and manifested by elevated concentrations of circulating proinflammatory cytokines, including interleukin (IL)-1beta, IL-6, and tumor necrosis factor-alpha (TNF-alpha). However, the source of the cytokines that appear during exercise remains unknown. In this study, we examined exercise-induced changes in plasma cytokine concentrations and their corresponding mRNA expression in peripheral blood mononuclear cells. Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
8
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 30 publications
13
140
8
6
Order By: Relevance
“…Being certain that monocytes are the main source of Il-6 during common immune response during sepsis or local infections, the first hypothesis tested was that immune cells were responsible of IL-6 increase during exercise [166], but early different groups demonstrated that IL-6 mRNA in monocytes did not increase as a result of exercise [167,168]. These and other subsequent works clearly demonstrated that monocytes are not the source of the exercise-induced increase in plasma IL-6.…”
Section: Acute Changes Of Systemic Inflammatory Markers During and Afmentioning
confidence: 99%
“…Being certain that monocytes are the main source of Il-6 during common immune response during sepsis or local infections, the first hypothesis tested was that immune cells were responsible of IL-6 increase during exercise [166], but early different groups demonstrated that IL-6 mRNA in monocytes did not increase as a result of exercise [167,168]. These and other subsequent works clearly demonstrated that monocytes are not the source of the exercise-induced increase in plasma IL-6.…”
Section: Acute Changes Of Systemic Inflammatory Markers During and Afmentioning
confidence: 99%
“…However, many investigations have shown that the practice of moderate exercises induces a Th1 response, with production of pro-inflammatory cytokines 48,59,81 . Resistance exercises of moderate intensity induced a light systemic inflammatory response, which is characterized, at least partly, by increases in the serum levels of inflammatory cytokines, such as IL1β and TNF-α 95,96 . Keller et al 97 reported that the TNF-α super-expression returned to normal concentrations after 1h of acute swimming exercise in mice whose TNF-α (TNFR) gene receptor was deleted.…”
Section: Effect Of Physical Exercise In the Cytokine Productionmentioning
confidence: 99%
“…Given the pattern of expression of eNOS, which is regulated not only at the transcriptional level but also posttranscriptionally (25), it is possible that complex interactions between different endogenous mediators released acutely during exercise constitute the stimulus for several chronic adaptations. High-intensity exercise, as used in the above-mentioned study of Miyauchi et al (34), elicits the release of proinflammatory cytokines such as tumor necrosis factor-␣ (TNF-␣), interleukin (IL)-1␤, and IL-6 (35,40,56). Interestingly, it has been shown that TNF-␣ induces a downregulation of eNOS, which results from a destabilization of eNOS mRNA with no effect on transcription (25,60).…”
Section: Exercise Training and Renal Vascular Reactivitymentioning
confidence: 99%